Geomagnetic ground survey in Slovakia for the 2007.5 epoch - DOLINSKÝ, Peter; VALACH, Fridrich; VÁCZYOVÁ, Magdaléna; HVOŽDARA, Milan (Contributions to Geophysics and Geodesy, 2009)
New geomagnetic ground survey was carried out in years 2006–2008. The survey was accomplished under fair geomagnetic-activity conditions during the minimum phase of a solar activity cycle No. 23. The measurements of the geomagnetic ﬁeld were reduced to the 2007.5 epoch using magnetograms of the Hurbanovo Geomagnetic Obser- vatory. The distribution of the geomagnetic ﬁeld over the territory of Slovakia is presented in the paper in terms of isoline contour maps of the northern, eastern, and vertical geomagnetic components together with the total magnetic intensity. The map of magnetic declination is added because of its practical importance. In addition, the maps of the normal geomagnetic ﬁeld represented by ﬁrst-degree polynomial model are shown here. The maps are also available on the web site http://www.geomag.sk/GMP/MagnMapsSk. Data of some nearby repeat stations in the adjoining countries were also employed in order to create the isoline contour maps.